2017
DOI: 10.1063/1.4978526
|View full text |Cite
|
Sign up to set email alerts
|

High-space resolution imaging plate analysis of extreme ultraviolet (EUV) light from tin laser-produced plasmas

Abstract: With the advent of high volume manufacturing capabilities by extreme ultraviolet lithography, constant improvements in light source design and cost-efficiency are required. Currently, light intensity and conversion efficiency (CE) measurments are obtained by charged couple devices, faraday cups etc, but also phoshpor imaging plates (IPs) (BaFBr:Eu). IPs are sensitive to light and high-energy species, which is ideal for studying extreme ultraviolet (EUV) light from laser produced plasmas (LPPs). In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The angular distribution is required to obtain CE from laser energy as estimated by eq 2. where E(45), I(45), and LE, are energy at 45°, IP signal at 45°, and irradiated laser energy, respectively. The E(45) value was registered by the calorimeter to be 4.0 × 10 −5 J/sr, according to the same condition as the previous research for tin targets, 40 where the ratio of inband (10−20 nm) per out band (longer than 20 nm) emission was 1:1.8. 10 The CE values for the reference metals were 1.35 and 0.04% for Sn and Li, respectively, for the second shots.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The angular distribution is required to obtain CE from laser energy as estimated by eq 2. where E(45), I(45), and LE, are energy at 45°, IP signal at 45°, and irradiated laser energy, respectively. The E(45) value was registered by the calorimeter to be 4.0 × 10 −5 J/sr, according to the same condition as the previous research for tin targets, 40 where the ratio of inband (10−20 nm) per out band (longer than 20 nm) emission was 1:1.8. 10 The CE values for the reference metals were 1.35 and 0.04% for Sn and Li, respectively, for the second shots.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Before we discuss the material-dependent EUV emission, we will summarize the first and the second shots. In the previous study for Sn, the difference was observed mainly for the first and later shots, the third and fourth shots gave almost the same data as the second, and then, we focus on the second shots in the present study. As for the alloy sample, the thickness is only 2 μm, and the third shot will reach to the Cu substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The EUV spectra were characterized as a strong unresolved transmission array (UTA) emission around 13.5 nm arising from tin transmissions between Sn 8+ and Sn 21+ 35 . The in-band CE at 13.5 nm 2% bandwidth was estimated at 0.8% for the 6-layer SnO 2 microcapsules using a previously described technique 37 . This was lower than the ideal CE (3%) for bulk tin 38 , but comparable to that of bulk tin (1%) at the same laser condition.…”
mentioning
confidence: 99%
“…Ga : Sn alloys of differing atomic (at%) ratios were synthesized, then characterized using differential scanning calorimetry (DSC) and scanning electron microscopy (SEM) with X-ray dispersive spectroscopy (EDS). A Nd:YAG laser (1 ns, 2 mJ) was used to generated EUV under similar conditions to previous work, 15 with a grazing incidence spectrometer (GIS). As an example, we show that EUV emission intensity for the Ga : Sn alloy was equal to bulk Sn, depending on the alloy composition.…”
mentioning
confidence: 99%